2016
DOI: 10.1142/9789813109698_0002
|View full text |Cite
|
Sign up to set email alerts
|

International Trade and Firm Performance: A Survey of Empirical Studies since 2006

Abstract: The literature on international trade and firm performance grows exponentially. This paper attempts to summarize what we learn from this literature to guide both future empirical and theoretical work in this area, and public debates and policy makers, in an evidence-based way. The focus is on the empirical part of the literature that consists of recently published papers using data for firms from manufacturing or services industries to study the links between international trade (exports and imports) and dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 45 publications
3
76
0
Order By: Relevance
“…A number of recent macro-level studies have found that the industries that are more integrated in international goods markets benefit from international diversification and are less exposed to domestic economic conditions (Braun and Raddatz 2007;Wagner 2013). Similarly, a parallel strand of micro-level literature suggests that the firms involved in international trade are more efficient and productive and have higher survival chances than the purely domestic firms (see, for example, a literature survey by Wagner (2012)). Thus, internationally trading borrowers are less likely to default on bank loans, decreasing the overall bank risk.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…A number of recent macro-level studies have found that the industries that are more integrated in international goods markets benefit from international diversification and are less exposed to domestic economic conditions (Braun and Raddatz 2007;Wagner 2013). Similarly, a parallel strand of micro-level literature suggests that the firms involved in international trade are more efficient and productive and have higher survival chances than the purely domestic firms (see, for example, a literature survey by Wagner (2012)). Thus, internationally trading borrowers are less likely to default on bank loans, decreasing the overall bank risk.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…A survey on early empirical evidence on the relationship between firm productivity and exporting was provided by Tybout (2003), while extensive summaries of more recent empirical evidence for this relationship in particular countries were offered by Wagner (2007;2012). According to the first survey by Wagner (2007), a large number of studies using data from different countries shows that exporters and importers are more productive than non-exporters and non-importers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…How are imports linked to firm performance? '', and the links between trade and other dimensions of firm performance besides productivity (including profitability, wages, and firm survival) were investigated [see Wagner (2012b) for a survey]. In this literature a typical data set used is based on either census-type data collected regularly by official statistics or on large comprehensive surveys of firms from other sources.…”
Section: Motivationmentioning
confidence: 99%